2017
DOI: 10.3847/1538-3881/aa5cb6
|View full text |Cite
|
Sign up to set email alerts
|

EPIC 219388192b—An Inhabitant of the Brown Dwarf Desert in the Ruprecht 147 Open Cluster

Abstract: We report the discovery of EPIC 219388192b, a transiting brown dwarf in a 5.3 day orbit around a member star of Ruprecht 147, the oldest nearby open cluster association, which was photometrically monitored by K2 during its Campaign 7. We combine the K2 time-series data with ground-based adaptive optics imaging and high-resolution spectroscopy to rule out false positive scenarios and determine the main parameters of the system. EPIC 219388192b has a radius of 1.01 0.03 R e , effective temperature T eff =5850… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 77 publications
3
45
0
Order By: Relevance
“…The resulting probabilities are listed in Table 5 for each candidate. The two faint candidates identified beyond 7 from EPIC 219388192 by Nowak et al (2017) were found to likely be background sources, with probabilities <15% of being physically associated. With the exception of the wider candidate around 70 Vir, most other candidates were found to have very high probabilities of being bonafide companions: the close candidates around 70 Vir, EPIC 219388192, HD 89744 and KELT-1 have >99% probabilities of being bound.…”
Section: Literature Search and Imaging Surveysmentioning
confidence: 95%
“…The resulting probabilities are listed in Table 5 for each candidate. The two faint candidates identified beyond 7 from EPIC 219388192 by Nowak et al (2017) were found to likely be background sources, with probabilities <15% of being physically associated. With the exception of the wider candidate around 70 Vir, most other candidates were found to have very high probabilities of being bonafide companions: the close candidates around 70 Vir, EPIC 219388192, HD 89744 and KELT-1 have >99% probabilities of being bound.…”
Section: Literature Search and Imaging Surveysmentioning
confidence: 95%
“…In fact, the recently discovered transiting brown dwarf in the significantly older Ruprecht 147 cluster similarly exhibits a relatively high eccentricity and short orbital period (Nowak et al 2017).…”
Section: Tidal Circularizationmentioning
confidence: 99%
“…Figure 13 shows the phase-folded and GPdetrended light curve: the primary eclipse is well-fit, although there is a modest increase in the residual scatter, which is larger than in AD 2615 but smaller than in AD 3814. The RV data suggest a moderately eccentric orbit (ẽ 0.15; see Figure 14) with a systemic velocity of = Nowak et al 2017;Bayliss et al 2017) and the primary component is one of only three M-dwarfs known to host a transiting brown dwarf. Furthermore, this is only the second known transiting brown dwarf in an open cluster (i.e., where the age is well-constrained), and the first younger than a Gyr.…”
Section: Ad 3116mentioning
confidence: 99%
“…As part of the ongoing RV follow-up program of K2 transiting planets successfully carried out by our consortium KESPRINT (e.g., Sanchis-Ojeda et al 2015;Grziwa et al 2016;Van Eylen et al 2016;Fridlund et al 2017;Guenther et al 2017;Nowak et al 2017), we herein present the results of an intensive RV campaign we conducted with the FIES, HARPS, and HARPS-N spectrographs to accurately measure the masses of the two small planets transiting HD 3167. The paper is organized as follows.…”
mentioning
confidence: 99%